2019
DOI: 10.24966/cmph-1978/100047
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Harassment and Depression in Mental Health Nurses: A National Survey from Cyprus

Abstract: Background: Workplace harassment constitutes a significant occupational hazard in many industries including the healthcare sector. The aim of our study was to evaluate workplace harassment and explore its potential association with depressive symptoms among mental health nurses. Methodology:A national survey among mental health nurses was conducted in Cyprus using three international validated questionnaires; namely the Leymann Inventory of Psychological Terror (LIPT), evaluating "mobbing" in the workplace, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…This study is somewhat similar to a previous study that reported that 10.6% of victims were bullied rarely, while 0.5% were bullied on a daily basis [3]. In addition, a European study reported that 4.1% of participants reported exposure to bullying or harassment at work [81]. Moreover, a prospective follow-up study regarding self-labeled workplace bullying cited that 6.1% of employees reported being bullying now and then, and 1.4% experienced bullying at work on a daily to monthly basis [71].…”
Section: Discussionsupporting
confidence: 90%
“…This study is somewhat similar to a previous study that reported that 10.6% of victims were bullied rarely, while 0.5% were bullied on a daily basis [3]. In addition, a European study reported that 4.1% of participants reported exposure to bullying or harassment at work [81]. Moreover, a prospective follow-up study regarding self-labeled workplace bullying cited that 6.1% of employees reported being bullying now and then, and 1.4% experienced bullying at work on a daily to monthly basis [71].…”
Section: Discussionsupporting
confidence: 90%